ANALISIS KOMPARATIF KINERJA KEUANGAN PERBANKAN MILIK NEGARA DAN MILIK SWASTA DI MASA PANDEMI COVID-19 - Tri Setiawati; Diah Agustina Prihastiwi (Jurnal Ilmiah Raflesia Akuntansi, 2022)
This research’s aim is to compare the financial performance between state-owned banks and national private banks during the Covid-19 pandemic which is projected by the ratio of LDR, NPL, NIM, BOPO, CIR, ROA, ROE, and CAR. Purposive sampling method was used in the selection of samples. The sample banks of this research are four state-owned banks and nine national private banks. The research data were analyzed using Independent Sample T-Test and Mann Whitney U-Test. According to the results of hypothesis test conducted, financial performance of state-owned banks and national private banks during the Covid-19 pandemic did not show any significant differences in terms of the ratio of LDR, NPL, NIM, BOPO, CIR, ROA, and ROE. However, if projected with the CAR ratio, it shows the results that there is a significant difference between the financial performance of state-owned banks and national private banks during the Covid-19 pandemic.